Penerapan Metode SAW (Simple Aditive Weight) Dan AHP (Analitical Hirarchi Process) Dalam Menentukan Kategori Penduduk Miskin - Suryati Suryati (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
Residents are all people who are domiciled in the territory of the Unitary State of the Republic of Indonesia for 1 year or more or those who are domiciled for less than 1 year (2020 Population Census concept). Based on the mandate of the 1945 Constitution, especially articles 33 and 34, the state is responsible for protecting the entire Indonesian nation and promoting general welfare in the context of realizing social justice for all Indonesian people. To facilitate interpretation, changes in welfare levels were assessed according to ten (10) criteria for poverty, with the variables set by the Social Service and the Central Statistics Agency.Poverty is a condition of limited ability to meet the needs of a decent life such as limitations in income, skills, health conditions, mastery of economic assets, or access to information. Measurement with a monetary approach can be done using expenditure data as an approach to household income. Then this expenditure data is compared with a limit of the rupiah exchange rate needed to meet the minimum living needs. This limit is often referred to as the poverty line. There are various indicators in determining the poor population, namely based on the status of the house, occupation, number of dependents, fuel for cooking, water sources, and electricity. Determining the poor has problems because they have to sort the data values of each data sheet in the form of paper,The decision support system using the Simple Additive Weighting (SAW) and Analytical Heirarchy Process (AHP) method takes a case study in Sembawa sub-district. The decision support system can assist decision makers in Sembawa District in determining the poor, and can be used as a basis for providing assistance. Keywords : DSS, SAW, AHP, Poor, Criteria, weight.